2013
DOI: 10.1007/s00223-013-9775-x
|View full text |Cite
|
Sign up to set email alerts
|

Intracortical Bone Remodeling Variation Shows Strong Genetic Effects

Abstract: Intracortical microstructure influences crack propagation and arrest within bone cortex. Genetic variation in intracortical remodeling may contribute to mechanical integrity and, therefore, fracture risk. Our aim was to determine the degree to which normal population-level variation in intracortical microstructure is due to genetic variation. We examined right femurs from 101 baboons (74 females, 27 males; aged 7–33 years) from a single, extended pedigree to determine osteon number, osteon area (On.Ar), havers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 45 publications
2
25
1
Order By: Relevance
“…Thus, much translational research, such as development of drugs and vaccines for a wide array of conditions including cardiovascular (Shen 2010), neurodegenerative (Schneider et al 2013), infectious (Zompi and Harris 2012), and skeletal diseases (Smith et al 2009), have been conducted with NHPs. As observed in humans, an important feature of NHP bone is the presence of osteonal or Haversian remodeling in cortical bone (i.e., intracortical bone remodeling), which is not normally present in rodent bone (Jerome and Peterson 2001; Havill et al 2013). Baboons are also more similar to humans in regard to cellular response after fracture, microstructural and compositional properties, bone mineral density, organic density, bone volume fraction, and length of collagen-mineral bundles as compared to dogs, cows, and rabbits (Wang et al 1998).…”
Section: Introductionmentioning
confidence: 95%
“…Thus, much translational research, such as development of drugs and vaccines for a wide array of conditions including cardiovascular (Shen 2010), neurodegenerative (Schneider et al 2013), infectious (Zompi and Harris 2012), and skeletal diseases (Smith et al 2009), have been conducted with NHPs. As observed in humans, an important feature of NHP bone is the presence of osteonal or Haversian remodeling in cortical bone (i.e., intracortical bone remodeling), which is not normally present in rodent bone (Jerome and Peterson 2001; Havill et al 2013). Baboons are also more similar to humans in regard to cellular response after fracture, microstructural and compositional properties, bone mineral density, organic density, bone volume fraction, and length of collagen-mineral bundles as compared to dogs, cows, and rabbits (Wang et al 1998).…”
Section: Introductionmentioning
confidence: 95%
“…This preferential adaptation for shear strains has been called the "shear resistance-priority hypothesis," which is based on the relatively deficient mechanical properties of bone loaded in shear when compared with tension and compression (Skedros, 2012;Skedros et al, 2015). This is an important consideration; attempts at correlating load history with regional variations in histomorphological characteristics (i.e., between regions of the same cross-section) may be unsuccessful if it is anticipated that unidirectional bending is sufficient for evoking regional differences in matrix adaptations when the habitual loading is actually much more complex (i.e., shear strains are prevalent and diffusely distributed; Figure 1; Goldman et al, 2003;Havill et al, 2013;Mayya et al, 2013;Skedros, 2012;Skedros et al, 2015). In other words, the shear-related histomorphological adaptations in these bones do not exhibit the more obvious marked regional variations in the matrix ultrastructural anisotropy (e.g., predominant CFO) seen in bones that receive habitual bending.…”
mentioning
confidence: 99%
“…It has been argued that this is the reason why in bones that are habitually torsionally loaded the relationships of CFO and other histomorphological characteristics are less clear with respect to load history even when unidirectional bending coexists (Rubin et al, 2013;Skedros, 2012). In this context, it is notable that "highcomplexity" best characterizes the load histories of the regions of limb bones that are typically evaluated in anthropological studies of cortical bone histomorphology (Burr et al, 1990;Carando et al, 1989;Cooper et al, 2007;Demes et al, 2001;Feik et al 1996;Havill, 2004;Havill et al, 2013;Hillier and Bell, 2007;Martiniakov a et al, 2006;Miszkiewicz, 2016;Mulhern and Van Gerven, 1997;Paine and Godfrey, 1997;Pfeiffer et al, 2006;Portigliatti et al, 1984;Schaffler and Burr, 1984;Sinclair et al, 2013;Skedros et al, 2015;Urbanov a and Novotn y, 2005;Warshaw, 2008). This is an important consideration; attempts at correlating load history with regional variations in histomorphological characteristics (i.e., between regions of the same cross-section) may be unsuccessful if it is anticipated that unidirectional bending is sufficient for evoking regional differences in matrix adaptations when the habitual loading is actually much more complex (i.e., shear strains are prevalent and diffusely distributed; Figure 1; Goldman et al, 2003;Havill et al, 2013;Mayya et al, 2013;Skedros, 2012;Skedros et al, 2015).…”
mentioning
confidence: 99%
“…Recent study of cortical bone of the femoral neck region has reported a significant negative association between On.Ar and age (Tong et al, 2015), while another study reports a negative association between On.Ar and body weight, but not age (Britz et al, 2009). In a study of femora from a single baboon lineage, genetic effects account for 48 to 75% of phenotypic variance in On.Ar (Havill et al, 2013). Insofar as osteon population density (OPD) reflects tissue remodeling, On.Ar should be directly correlated with OPD, with smaller secondary osteons filling less of the rib cross‐section space if bone turnover and cortical area are held constant.…”
mentioning
confidence: 99%